Violence, gender and justice - Wykes, Maggie, 1951-; Welsh, Kirsty; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2009)
This comprehensive text provides an overview of the relationship between violence, gender, crime and justice. It brings together theory with contemporary cases to enable the reader to understand the key concepts, issues and connections involved.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Violence in men; Men -- Crimes against; Violence; Violence in women; Women -- Crimes against; Sex discrimination in criminal justice administration; Electronic books